PWE-047 When Should I Take Terminal Ileal Biopsies? Experience From A Single Unit. (9th June 2014) - Neilson, LJ; Bevan, R; Rees, CJ
Abstract : Introduction: Terminal ileum (TI) intubation at colonoscopy may be useful in the investigation of patients with diarrhoea or possible inflammatory bowel disease (IBD). 1, 2 The yield of TI biopsies is variable and there are no standards for current practice. 2, 3 Furthermore, in the UK concerns remain regarding the potential for prion transmission. Methods: We aim to establish the yield of TI biopsies in a single unit. All TI biopsies recorded on the pathology system in a 3-year period were reviewed. Colonoscopy reports and case notes were reviewed to establish if biopsy results were clinically relevant (defined as altering management). Statistical analysis was performed using SPSS. P values were calculated using Fisher's exact test to show any difference in biopsy yield between normal and abnormal looking mucosa for each indication. The values were calculated for all abnormal biopsy results and clinically relevant biopsy results. Results: 129 TI biopsies were taken between September 2010 and September 2013, 49 (38%) male and 80 (62%) female. Mean age 44 years (s.d. 17.2). There were 29 (22.5%) cases of known IBD. 5 (3.9%) cases were completion colonoscopies after colorectal cancer surgery where TI biopsies are taken to prove a complete examination. Conclusion: We demonstrate that when investigating patients with diarrhoea, abdominal pain or IBD, if the terminal ileum is visually normal, biopsies do not add to the clinical picture. There is a higher yield of relevant biopsy abnormalities when the TI appears abnormal. We can recommend within our practice that visual assessment of a normal terminal ileum is adequate, thereby reducing unnecessary biopsies. This reduces the workload for pathology laboratories, reduces risk from biopsies and improves patient care as normal results can be communicated sooner to the patient. References: 1 Morini S, et al . Retrograde ileoscopy in chronic nonbloody diarrhea: a porspective, case-control study. Am J Gastroenterol 2003;98(7):1512–15 2 Geboes K, et al . Is ileoscopy with biopsy worthwhile in patients presenting with symptoms of inflammatory bowel disease? Am J Gastroenterol 1998;93(2):201–206 3 Melton SD, et al . Ileal biopsy:Clinical indications, endoscopic and histopathologic findings in 10, 000 patients. Dig Liver Dis 2011;43(3):199–203 Disclosure of Interest: None Declared.